2011
DOI: 10.5465/amj.2011.59215085
|View full text |Cite
|
Sign up to set email alerts
|

The Necessity of Others is The Mother of Invention: Intrinsic and Prosocial Motivations, Perspective Taking, and Creativity

Abstract: Although many scholars believe that intrinsic motivation fuels creativity, research has returned equivocal results. Drawing on motivated information processing theory, we propose that the relationship between intrinsic motivation and creativity is enhanced by other-focused psychological processes. Perspective taking, as generated by prosocial motivation, encourages employees to develop ideas that are useful as well as novel. In three studies, using both field and lab data, we found that prosocial motivation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
1,102
2
29

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,193 publications
(1,184 citation statements)
references
References 72 publications
(167 reference statements)
51
1,102
2
29
Order By: Relevance
“…If our theory is correct, perceived effect on others should mediate the moderating role of the salience of interpersonal impact in the effect of cognitive control impairment on socially desirable behaviors. Figure 3 depicts the implied meditational model (for other research using this analytical approach see, e.g., Grant & Berry, 2011;Pitesa & Thau, 2013). Specifically, our theory implies that an increased salience of interpersonal impact (our manipulation) should lead to a higher perceived effect on others.…”
Section: Studymentioning
confidence: 99%
“…If our theory is correct, perceived effect on others should mediate the moderating role of the salience of interpersonal impact in the effect of cognitive control impairment on socially desirable behaviors. Figure 3 depicts the implied meditational model (for other research using this analytical approach see, e.g., Grant & Berry, 2011;Pitesa & Thau, 2013). Specifically, our theory implies that an increased salience of interpersonal impact (our manipulation) should lead to a higher perceived effect on others.…”
Section: Studymentioning
confidence: 99%
“…Whereas altruistic individuals perform helpful acts with no expectation of personal gain, prosocial motivation can benefit the helper as well as the target. In describing how prosocial motivation diverges from altruism Grant and Berry (2011) write, "employees can desire to help others because they care about them, because they feel it is the right thing to do, because they wish to maintain membership in a valued group, and/or because doing so will make them feel good about themselves" (p. 77). These arguments are supported by evidence from the mentoring literature, which suggests that for experienced senior organizational members, providing junior colleagues with support and career counsel also fulfills self-motivations (e.g., reducing workload, identity affirmation, and preserving self-worth; Janssen, van Vuuren, & de Jong, 2014).…”
Section: Characteristics Of Managerial Leadersmentioning
confidence: 99%
“…Again, prosocial motivation does not necessarily exclude benefits for the actor, but prosocially motivated individuals have a desire to aid others (Grant 2007;Grant and Berry 2011). Similarly, we proposed that although health entrepreneurship may create profit for entrepreneurs, it is also highly likely to improve others' health.…”
Section: Entrepreneurial Motivation and Others' Healthmentioning
confidence: 99%
“…Prosocial motivation influences cognitive processing (Kunda 1990;Nickerson 1998). Grant and Berry (2011) found that prosocial motivation can lead to perspective taking, which enables people to generalize valuable ideas in more creative ways. Perspective taking is "a cognitive process in which individuals adopt others' viewpoints in an attempt to understand their preferences, values, and needs".…”
Section: Entrepreneurial Motivation and Others' Healthmentioning
confidence: 99%